2015
DOI: 10.1111/eff.12248
|View full text |Cite
|
Sign up to set email alerts
|

Potential direct and indirect effects of climate change on a shallow natural lake fish assemblage

Abstract: This Article is brought to you for free and open access by the Natural Resources, School of at DigitalCommons@University of Nebraska -Lincoln. It has been accepted for inclusion in Papers in Natural Resources by an authorized administrator of DigitalCommons@University of Nebraska -Lincoln.Breeggemann, Jason J.; Kaemingk, Mark A.; DeBates, Timothy J.; Paukert, Craig P.; Krause, Jacob R.; Letvin, Alexander P.; Stevens, Tanner M.; Willis, David W.; and Chipps, Steven R., "Potential Direct and Indirect Effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…However, since fish were sampled from the same population, this background rate is likely the same for fish subjected to each gear and should not influence comparisons between gears. The injuriousness of tubes has not been as thoroughly reported in current literature, but given the widespread use of tubes to sample stomach contents (Raborn et al 2002;Trippel et al 2015;Breeggemann et al 2016), the injuries reported in this study, and the potential for delayed mortality, this is an important issue that should be addressed in future research. Previous studies have found lavage to be a rather benign procedure, in terms of both injury (Haley 1998) and mortality (Light et al 1983;Hakala and Johnson 2004), and the current study supports those findings for Butterfly Peacock Bass.…”
supporting
confidence: 89%
“…However, since fish were sampled from the same population, this background rate is likely the same for fish subjected to each gear and should not influence comparisons between gears. The injuriousness of tubes has not been as thoroughly reported in current literature, but given the widespread use of tubes to sample stomach contents (Raborn et al 2002;Trippel et al 2015;Breeggemann et al 2016), the injuries reported in this study, and the potential for delayed mortality, this is an important issue that should be addressed in future research. Previous studies have found lavage to be a rather benign procedure, in terms of both injury (Haley 1998) and mortality (Light et al 1983;Hakala and Johnson 2004), and the current study supports those findings for Butterfly Peacock Bass.…”
supporting
confidence: 89%
“…This response of whitespotted conger to temperature might be related to various ecological processes, for example, temperature may directly affect metabolic and physiological processes then determine growth rates (Boltana et al 2017). Besides, the effects can also be caused indirectly by altering sh assemblage structure and productivity of ecosystems through food web mechanisms (Pörtner and Peck 2010;Breeggemann et al 2015), which determine the prey availability and consequently growth. For many marine sh species, a slight increase in their thermal window is likely to bene t growth (Thresher et al 2011;Tao et al 2018).…”
Section: Discussmentioning
confidence: 99%
“…Interspecific competition, predation, and other factors play a key role in maintaining community structure (Glasser 1979;Robertson 1996;Aschan et al 2013). Therefore future studies should begin to consider multiple species and community level reactions to climate change (Poulard and Blanchard 2005;Breeggemann et al 2015;MacDonald et al 2015).…”
Section: Model Limitationsmentioning
confidence: 99%